Gaudium et Spes: between pastoral character an prescriptive obligatory = Gaudium et Spes : entre caractère pastoral et obligation imposée = Gaudium et spes : tra il carattere pastorale ed il dovere imposto - Přibyl, Stanislav (Philosophy & canon law, 2016)
In the 1983 Code of Canon Law, Pope Saint John Paul II states that the Code is especially inspired by the Second Vatican Council constitution, that is, the Dogmatic Constitution Lumen Gentium and the Pastoral Constitution Gaudium et Spes. The second constitution does not have to be a source of inspiration to the formulation of legal norms. However, we can find there some support for future canonical regulations. This concerns, in particular, the extension of the idea of marriage which inspired the Code that defines, anew, the dissolution of marriage and clarifies the relations between the state and the Church on the basis of which the concordate law is developed in the post-Second Vatican Council times.